The Distribution of Goat Gastrointestinal Tractus Worm Egg at Rambon District of Nganjuk Regency - Arum Puspitasari; Boedi Setiawan; Setiawan Koesdarto; Kusnoto Kusnoto; Soeharsono Soeharsono; Poedji Hastutiek (Journal of Parasite Science (JoPS), 2019)
This study aims to determine the distribution of worm tract infection in foat digestion in Sub-district of Prambon, Nganjuk Regency. This research was conducted in Agustus 2018-Januari 2019 with 108 samples of stool examination iin laboratory of Helmintologi Airlangga University Department of Parasitology, were examinated by native, sedimentation. Floatation techniques, and distribution of worm types of feces. The results showed that 66 samples were positive infected by gastrointestinal worm, its indicated that helminthiasis was 61,11%. On examination it was found some kind of worm eggs, which are: Oesophagustomum spp., Bunostomum spp., Haemonchus spp., Trichostrongylus spp., Strongyloides spp., Trichuris spp., Chabertia spp and Moniezia benedini. The results of study showed the most of worm distribution in feces is Haemonchus spp.